The Typology of Islamic Social Entrepreneurship: Principles, and Characteristic from a Maqashid Shariah Perspective - Setiawan, Muhammad Agus; Armina, Sheema Haseena; Novika, Syahrin (Ijtihad, 2024)
**English**This research aims to explore the typology of Islamic Social Entrepreneurship (ISE) through its definition, principles and characteristics from the perspective of Maqashid Shariah. Maqashid Shariah, as the ultimate goal of Islamic law, provides a framework for developing an entrepreneurship model that focuses not only on economic gains but also social and moral benefits. ISE differs from conventional entrepreneurship as it emphasizes the balance between economic needs and social welfare based on Islamic teachings. The research method used is a qualitative method with theoretical analysis and empirical studies to define the ISE typology. The results show that the ISE typology includes the protection of religion through the establishment of Islamic educational institutions, Islamic media publishing, and Islamic study centers, the protection of the soul through the provision of Islamic health services, social and charitable institution programs, and community welfare programs, and the protection of wealth through Islamic banking and finance, waqf-based businesses, and Islamic social investment. Based on the results of the ISE typology, ISE can make a practical contribution by offering guidance for businesses and policy makers in developing ISE according to Islamic principles. Theoretically, the typology enriches the literature on ISE and Maqashid Shariah, providing a clearer framework for the classification and development of social entrepreneurship models that comply with Islamic values. This research emphasizes the importance of a holistic approach that combines theoretical analysis and empirical studies to define a typology of ISEs, as well as providing practical guidelines for implementation in the field.                                                    **Indonesia**Penelitian ini bertujuan mengeksplorasi tipologi Islamic Social Entrepreneurship (ISE) melalui definisi, prinsip, dan karakteristiknya dari perspektif Maqashid Syariah. Maqashid Syariah, sebagai tujuan utama hukum Islam, menyediakan kerangka kerja untuk mengembangkan model kewirausahaan yang tidak hanya berfokus pada keuntungan ekonomi tetapi juga manfaat sosial dan moral. ISE berbeda dari kewirausahaan konvensional karena menekankan keseimbangan antara kebutuhan ekonomi dan kesejahteraan sosial berdasarkan ajaran Islam. Metode penelitian yang digunakan adalah metode kualitatif dengan analisis teoretis dan studi empiris untuk mendefinisikan tipologi ISE. Hasil penelitian menunjukkan bahwa Tipologi ISE meliputi perlindungan agama melalui pendirian lembaga pendidikan Islam, penerbitan media Islami, dan pusat kajian Islam, perlindungan jiwa melalui pemberian layanan kesehatan Islami, program lembaga sosial dan amal, serta program kesejahteraan komunitas, serta perlindungan harta melalui perbankan dan keuangan syariah, bisnis berbasis waqf, dan investasi sosial Islami. berdasarkan hasil dari tipologi ISE, ISE dapat memberikan kontribusi praktis dengan menawarkan panduan bagi pelaku usaha dan pembuat kebijakan dalam mengembangkan ISE sesuai prinsip Islam. Secara teoretis, tipologi ini memperkaya literatur tentang ISE dan Maqashid Syariah, memberikan kerangka kerja yang lebih jelas untuk klasifikasi dan pengembangan model social entrepreneurship yang sesuai dengan nilai-nilai Islam. Penelitian ini menekankan pentingnya pendekatan holistik yang menggabungkan analisis teoretis dan studi empiris untuk mendefinisikan tipologi ISE, serta menyediakan panduan praktis untuk implementasi di lapangan.